The validity of Francisco Suarez’s Philosophy of Law in the Spanish Silver Age - Delia Manzanero (Pensamiento. Revista de Investigación e Información Filosófica, 2018)
The present article seeks to present the revitalization that occurs during the Spanish Silver Age of the topics and the juridical methodology of the Spanish Natural Law Classics, which has in the Jesuit philosopher and theologian Francisco Suarez, one of the prime leading figures. In order to deal with this stage of revitalization of the iusnaturalist Suarezian theses and their repercussions in the Spanish Natural Law Philosophy that unfolds during the last third of the nineteenth century and the first decades of the twentieth century, we will emphasize the concomitances between the nineteenth-century Krausists and those who lived the magni Hispani, to reach what we consider to be an indispensable link in this phase of recovery of the Natural Law theory: the substantial reading on Francisco Suarez’s legal work made by the iusphilosopher Recasens Siches, where we can appreciate the suggestive inspiration contained in the work of our great Spanish classic and where it develops a renew iusnaturalist conception appropriate for our present time.